1999
DOI: 10.1021/la990025f
|View full text |Cite
|
Sign up to set email alerts
|

Chromatic Studies of a Polymerizable Diacetylene Hydrogen Bonding Self-Assembly:  A “Self-Folding” Process To Explain the Chromatic Changes of Polydiacetylenes

Abstract: In the present study, a new diacetylene compound (PDATAZ), which readily forms a complementary hydrogen bonding self-assembly at the air−water interface or in the solid state with barbituric acid (BA) or cyanuric acid (CA), was designed and synthesized. The photopolymerization studies of PDATAZ and its assembly with BA or CA have revealed some important insights on the chromatic properties of polydiacetylenes. It was found that the chromatic property of polydiacetylenes is determined by whether the polymer cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
105
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(106 citation statements)
references
References 51 publications
1
105
0
Order By: Relevance
“…8 Leblanc et al proposed that extended radiation-induced chromatic changes of PDAs may arise from "selffolding" of the originally linear conjugation backbone into a zigzag structure (via the free rotation of single bonds) upon propagation of the polymer chain, resulting in a shortened π-electron delocalization. 31 In this study, the dramatic morphological transformation of BPDAs from ribbons to nanofibers accompanying the charge-induced CR (Fig. 5) suggest that both side chain disordering and disruption of main chain packing play important roles in the observed chromatic shift.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…8 Leblanc et al proposed that extended radiation-induced chromatic changes of PDAs may arise from "selffolding" of the originally linear conjugation backbone into a zigzag structure (via the free rotation of single bonds) upon propagation of the polymer chain, resulting in a shortened π-electron delocalization. 31 In this study, the dramatic morphological transformation of BPDAs from ribbons to nanofibers accompanying the charge-induced CR (Fig. 5) suggest that both side chain disordering and disruption of main chain packing play important roles in the observed chromatic shift.…”
Section: Discussionsupporting
confidence: 49%
“…7,8 A compromised explanation suggests that the alkyl side chains in the "red phase" remain in an ordered conformation, with only a slightly different packing mode from the "blue phase". 31 More recent investigation of the temperature dependence of visible absorption spectra and the electron diffractions of PDA films revealed that the electronic natures of the PDAs are strongly dependent on their resonance backbone structures as well as the stacking of the main chains. 8 Leblanc et al proposed that extended radiation-induced chromatic changes of PDAs may arise from "selffolding" of the originally linear conjugation backbone into a zigzag structure (via the free rotation of single bonds) upon propagation of the polymer chain, resulting in a shortened π-electron delocalization.…”
Section: Discussionmentioning
confidence: 99%
“…A superlinear increase in nonlinearities with a distinct change in slope, however, could arise from an increased ordering of the sample in solution, such as folding. [34] This prospect is discussed below.…”
Section: Full Papermentioning
confidence: 99%
“…Since the coloriometric change upon the binding of toxins seems to be caused by the reorientation of lipids and a reduction in the length of the conjugated lipid backbone due to distribution of the polymer network. 10 The reason for the change in fluorescence can be similarly speculated. Therefore, we consider that a reduction in the flexibility of the conjugated lipid backbone after the binding of proteins on the surface of the nanoparticles may lead to a decrease in fluorescence.…”
Section: Fluorescent Detection Of the Binding Of Lectin Onto Glyconanmentioning
confidence: 98%